Physicochemical and antioxidant changes of black sapote (Diospyros digyna, Ebenaceae) during on-tree fruit development - Merino-Sánchez, Liliana; Romero-Luna, Haydee Eliza; García-Barradas, Oscar; Mendoza-López, María Remedios; Jiménez Fernández, Maribel (Instituto de Ecología, A.C., 2022)
Background and Aims: The fruit of Diospyros digyna, known as black sapote, is an exotic fruit which is consumed and marketed in southern Mexico. It has been little studied and the changes in the profiles of its physicochemical and antioxidant properties during its development stage on the tree are unknown. Therefore, the objectives of this study were to 1) evaluate the physicochemical properties and antioxidant activity during development and ripening of D. digyna fruits, in order to know the changes of the fruit, and 2) establish the appropriate time of harvest of this climacteric fruit. Methods: Physical properties of the fruit D. digyna, including firmness, color, respiration rate of the whole fruit, as well as proximal composition, maturity index, and bioactive compounds including antioxidant activity of the pulp, were evaluated every two weeks during 14 weeks of fruit development on the tree. Key results: During this 14-week period of analysis, the weight and dimensions of the fruit of D. digyna increased by about 90%. Vitamin C content raised from 60 to 369 mg/100 g of fresh fruit. However, the concentration of total carotenoids, tannins, polyphenols, and the acidity and respiration rate decreased. The antioxidant activity determined by the percentage of DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging was 30%, together with a high reducing power (2.40 O.D.) at the end of the study. The fracture strength of the fruit peel and pulp was 1.40 N and 5.35 N, respectively. Conclusions: This study monitors the physical changes, in respiration, composition and antioxidant activity during the development of the D. digyna fruit on the tree, demonstrating that week 10 is the best harvest time, since there are no important changes from that moment. Likewise, it is confirmed that the black sapote can be an important source of vitamin C.